Health condition of Afghan refugees residing in Iran in comparison to Germany: a systematic review of empirical studies - Rahimitabar, Parisa; Kraemer, Alexander; Bozorgmehr, Kayvan; Ebrahimi Sadrabadi, Fatemeh; Takian, Amirhossein (International journal for equity in health, 2023)
The re-emerging dominance of the Taliban in Afghanistan in 2021 caused a new wave of Afghan refugees heading Iran and neighboring countries. Iran in the Middle East and Germany in Europe are two major host countries to the largest populations of Afghan refugees. In both countries, several studies have been done to assess the health condition of refugees.
Gesehen am 23.03.2023